ANALISIS DAMPAK NEW MEDIA DALAM PEMBENTUKAN IDENTITAS DIRI REMAJA - M Ravii Marwan (Asosiasi Dosen Muda Indonesia, 2023)
ABSTRACT New media encourages technological development, especially in the field of communication. Social media is known to continue to grow and have a good and bad impact on teenagers. The purpose of this study is to find out how social media can shape the identity of adolescents in society. Qualitative descriptive methods are used as methods of this research. This research uses symbiotic interaction theory and has data collection techniques, namely observation and literature review. The conclusions of the research and the data collection techniques used, it can be seen that what teenagers are currently displaying on social media is not the real self, but rather the result of self-construction that forms a new identity in front of social media users. It's good for today's teenagers to be more introspective in the use of social media, so that their views on a topic are not rigid but rather on considerations made so that the role of new media can be a positive thing. Keywords: Social media, Symbolic Interracation Theory, Public opinion, New Media